Spatial Distribution of the Attentional Blink - DU, FENG; Abrams, Richard; Zhang, Kan (Frontiers in Psychology, 2011)
In the present study subjects viewed streams of rapid serially presented characters and searched for a target digit. After presentation of the target digit, a second target consisting of an orientation singleton (Experiment 1) or a second digit (Experiment 2) was presented at one of several distances from the first target. The attentional blink impaired performance on the second target with the effect being strongest at distances somewhat removed from the first target location. These results are consistent with lateral inhibition theory and help to resolve some fundamental questions about the spatial distribution of the attentional blink.